Methods of maintaining turbine discs to avert critical bucket attachment dovetail cracks - WALSH JOHN; WILLIAMS ANDREW D; CALDER WILLIAM (2012)
Methods of to maintaining turbine discs prone to cracks in bucket attachment dovetails are disclosed. In one embodiment, wherein a turbine disc comprises a plurality of bucket attachment dovetail regions, one or more of the bucket attachment dovetail regions comprises a cooling slot, and each cooling slot comprises edges and adjacent surfaces, a method comprises inspecting the one or more of the bucket attachment dovetail regions comprising a cooling slot to confirm that each bucket attachment dovetail region meets predetermined minimum standards. The method further comprises blending the edges of the at least one of the cooling slots. The method further comprises polishing the edges of the at least one of the cooling slots. The method further comprises peening the edges of the at least one of the cooling slots. The method further comprises coating the edges and adjacent surfaces of at least one of the cooling slots.